INNOVATION BUSINESS MODEL OF VANILLA IN TAIWAN - Huang, Chia-Yin; Lin, Chin-Chiuan (International Journal of Application on Economics and Business, 2025)
Vanilla pod is one of the most expensive spice in the world. The international price is as high as 300 to 600 US dollars per kg of vanilla pods, therefore, vanilla planting has sprung up in various countries. The present study proposed an innovation business model of vanilla in Taiwan. The innovative business model based on the SID (supply-interface-demand) model and the 9 building blocks model, combines capital suppliers, land suppliers, labor providers, and case company to provides various combinations of cooperation modes for the four parties to choose their best cooperation programs. For the investors, the return rate for the first round of investment is about 13%; and the second round is about 25%. For the labors, they can have at least NT$ 40,000 per month and just need to work about 4 days per week. For land providers, every units of land they can received NT$ 20,000 per year. Because the innovation business model has very good business benefits not only for the case company but also for the investors, labors, and land providers. Therefore, the innovation business model proposed in the present study can be promoted and applied to relevant countries.